Transboundary Capital and Pollution Flows with Endogenous Wealth, Knowledge and Environment Accumulation - zhang, wei-bin (P2E-LIPI, 2016)
The paper deals with global dynamic interdependence between inequalities in income and wealth, economic structures, knowledge growth, capital accumulation, and environmental changes. It builds a trade model with endogenous wealth, environment, knowledge accumulation and labor and capital distribution between sectors and between countries under perfectly competitive markets and free trade. The model is built on the basis of the Solow-Uzawa neoclassical growth model, the Oniki-Uzawa trade model, some neoclassical growth models with environment, ideas about transboundary pollution in environmental economics, Arrowâs learning-by-doing model, and Zhangâs idea about knowledge as international public stock. We integrate these approaches by applying the utility function proposed in a unique manner by Zhang to determine saving and consumption. The dynamics of -country world economy is controlled by differential equations. We simulate the motion of the model with three countries and carry out comparative dynamic analysis with regard to some parameters.